2023
DOI: 10.3390/microorganisms11081938
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Microbiota Gender Differences in Subjects with Healthy Stomachs and Autoimmune Atrophic Gastritis

Abstract: Gender differences and microbiota are gaining increasing attention. This study aimed to assess gender differences in gastric bacterial microbiota between subjects with healthy stomachs and those with autoimmune atrophic gastritis. This was a post hoc analysis of 52 subjects undergoing gastroscopy for dyspepsia (57.7% healthy stomach, 42.3% autoimmune atrophic gastritis). Gastric biopsies were obtained for histopathology and genomic DNA extraction. Gastric microbiota were assessed by sequencing the hypervariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Women with healthy stomachs had reduced biodiversity but a two-fold higher gastric bacterial abundance compared to men. On the contrary, the bacterial abundance of AAG patients was not characterized by significant gender differences, possibly because of hypochlorhydria that halved the bacterial abundance in women and had a minimum impact on it in men [91].…”
Section: Aag and Hypochlorhydria: What Are The Consequences On The Ga...mentioning
confidence: 89%
See 1 more Smart Citation
“…Women with healthy stomachs had reduced biodiversity but a two-fold higher gastric bacterial abundance compared to men. On the contrary, the bacterial abundance of AAG patients was not characterized by significant gender differences, possibly because of hypochlorhydria that halved the bacterial abundance in women and had a minimum impact on it in men [91].…”
Section: Aag and Hypochlorhydria: What Are The Consequences On The Ga...mentioning
confidence: 89%
“…The composition of the gastric microbiota depends on many different factors. Pivetta et al [91] observed that there were differences between men's and women's gastric microbiota in both healthy stomachs and stomachs affected by AAG. Particularly, in healthy people, there was a lower biodiversity in females compared to that of males; instead, in patients affected by AAG, there was a significantly lower biodiversity in the males than in the females.…”
Section: Aag and Hypochlorhydria: What Are The Consequences On The Ga...mentioning
confidence: 99%